Application of geogebra in online learning for pattern recognition skills in analytical geometry courses - Eka Rachma Kurniasi; Yaya S Kusumah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This study aims to analyze the effect of GeoGebra implementation in online learning on students' pattern recognition skills in Analytical Geometry courses. This study used a quantitative method with a quasi-experimental design. Participants were students enrolled in an online Analytical Geometry class. The subjects taken were one class. The instruments used included a pattern recognition ability test consisting of 3 questions and an observation sheet for learning activities. Pattern recognition indicators are recognizing patterns, similarities, and connections. The results showed a significant effect of GeoGebra implementation on students' pattern recognition skills. The effect size calculation results showed a score of 0.99, which is included in the very large category. The overall mean score was 82.47 and the standard deviation was 7.12. The use of GeoGebra effectively helped students visualize abstract geometric concepts. Digital visualization through GeoGebra minimizes inaccuracies that often occur when drawings are created manually, thus enabling students to identify geometric patterns and regularities more clearly. Therefore, integrating GeoGebra into online learning not only improves conceptual understanding but also strengthens students' ability to recognize mathematical patterns in Analytical Geometry